Nonmulberry Silk Fibroin Scaffold Shows Superior Osteoconductivity Than Mulberry Silk Fibroin in Calvarial Bone Regeneration. Issue 11 (17th June 2015) - Sahu, Neety; Baligar, Prakash; Midha, Swati; Kundu, Banani; Bhattacharjee, Maumita; Mukherjee, Snehasish; Mukherjee, Souhrid; Maushart, Florian; Das, Sanskrita; Loparic, Marko; Kundu, Subhas C.; Ghosh, Sourabh; et al.
<x xml:space="preserve">Abstract</x> Recent years have witnessed the advancement of silk biomaterials in bone tissue engineering, although clinical application of the same is still in its infancy. In this study, the potential of pure nonmulberry Antheraea mylitta (Am) fibroin scaffold, without preloading with bone precursor cells, to repair calvarial bone defect in a rat model is explored and compared with its mulberry counterpart Bombyx mori (Bm) silk fibroin. After 3 months of implantation, Am scaffold culminates in a completely ossified regeneration with a progressive increase in mineralization at the implanted site. On the other hand, the Bm scaffold fails to repair the damaged bone, presumably due to its low osteoconductivity and early degradation. The deposition of bone matrix on scaffolds is evaluated by scanning electron and atomic force microscopy. These results are corroborated by in vitro studies of enzymatic degradation, colony formation, and secondary conformational features of the scaffold materials. The greater biocompatibility and mineralization in pure nonmulberry fibroin scaffolds warrants the use of these scaffolds as an "ideal bone graft" biomaterial for effective repair of critical size defects.